2021
DOI: 10.1128/msphere.00500-21
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Klebsiella Intestinal Colonization Density To Assess Infection Risk

Abstract: Colonization by bacterial pathogens often precedes infection and offers a window of opportunity to prevent these infections in the first place. Klebsiella colonization is significantly and reproducibly associated with subsequent infection; however, factors that enhance or mitigate this risk in individual patients are unclear. This study developed an assay to measure the density of Klebsiella colonization, relative to total fecal bacteria, in rectal swabs from hos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
0
19
1
Order By: Relevance
“…These observations support the notion that interventions aimed at preventing cross-transmission in hospitals (e.g., hand hygiene, or seek-and-contain approaches to CP infections) could have a significant impact on reducing the total burden of AMR infections. However, the data also suggest that the underlying burden of opportunistic K. pneumoniae infection, which originate from diverse strains present in the gut microbiome of patients, might still remain high unless this source of infection is specifically targeted (e.g., by colonization or colonization-density screening) 50 .…”
Section: Discussionmentioning
confidence: 99%
“…These observations support the notion that interventions aimed at preventing cross-transmission in hospitals (e.g., hand hygiene, or seek-and-contain approaches to CP infections) could have a significant impact on reducing the total burden of AMR infections. However, the data also suggest that the underlying burden of opportunistic K. pneumoniae infection, which originate from diverse strains present in the gut microbiome of patients, might still remain high unless this source of infection is specifically targeted (e.g., by colonization or colonization-density screening) 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal microbiomes with an increased Kp relative abundance are associated with an increased risk of Kp bacteremia, nosocomial transmission, and may predispose to prolonged colonization. 22 , 23 , 49 , 50 Accurate measurement of Kp abundance could therefore provide important clinical information relevant for infection risk stratification and infection control purposes. In our Kp spiked microbiomes, which contained ≤1% total Enterobacterales, we found WMS gave close estimations of Kp relative abundance to 0.01%, below which false positives began to have a substantial influence.…”
Section: Discussionmentioning
confidence: 99%
“…First, we have a highly heterogeneous patient population in terms of baseline clinical conditions as well as infection types. Sun et al showed that increased Klebsiella intestinal load (>22%) was significantly associated with subsequent all-site infections and with BSI but not with urinary tract and respiratory infections in an ICU setting ( 22 ). Second, we obtained a single determination of KPC-KP load at recruitment, so it is possible that we may have missed the highest relative load values prior to infection.…”
Section: Discussionmentioning
confidence: 99%
“…There are also limitations inherent to our qPCR approach for estimation of KPC-KP relative load in rectal swabs because this method does not account for bias derived from the potential presence of dead bacterial cells in rectal swabs or differences in target ( bla KPC ) and internal reference (16SrRNA) gene copy number between different bacterial cells or bacterial species. As an alternative, some studies have employed rRNA sequencing ( 18 , 22 ), which has the advantage of providing informative data about microbiota diversity. However, compared with rRNA sequencing, qPCR assays have the advantage that could be more readily translated into clinical practice because many clinical microbiology laboratories are proficient in the implementation of these assays.…”
Section: Discussionmentioning
confidence: 99%